New perspectives on pragmatism and analytic philosophy - Calcaterra, Rosa Maria. (Value Inquiry Book Series, 2011)
The strong influence of pragmatism in the early 20th-century international debate, its subsequent and apparently inexorable decline, and its recent revival are intertwined with the fate of other currents of thought that have marked the development of contemporary philosophy. This volume clarifies the most recent events of this development focusing on key theoretical issues common both to American classic philosophical tradition and analytical thought. Many essays in this volume belong to what we can call "new" pragmatism, namely a pragmatist perspective that is different from the postmodernist "neo" pragmatism à la Rorty. The volume shows that both pragmatists and analytic thinkers stress the importance of logic and scientific method in order to deal with philosophical problems and seek for a clarification of the relation between our ethical values and our understanding of natural facts. Moreover, the anti-skeptic attitude that characterizes pragmatism as well as most part of analytic philosophy, and their common attention to the problems of language and communication are emphasized. The more sophisticated tools for addressing both theoretical and methodological problems developed by analytic philosophy are pointed out, and the essays show the possible integration of these two forms of speculation that, for too a long time, mutually disregarded one another.